Cost variance of health services at PHC hospital, Surabaya, Indonesia: Operational audit - ROCHMAH, T.N; SUTIKNO, A.E; DAHLUI, M.; QOMARUDDIN, M.B (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The operational audit uses to explain cost variances that occurred in the delivery of healthcare services to inpatients utilizing the BPJS. This study aimed to identify cost variance between actual cost and set tariff for inpatients management of chronic ischemic heart disease, cerebral stroke, final-stage of renal disease, and diabetes mellitus type-2. This study had shown that cost containment via cost monitoring and cost management could be obtained. Variance cost of managing some diseases is unavoidable due to the unique patient's characteristics and different costing methods. Steps could be taken up to ensure the operations are performed effectively and efficiently.